THE ROLE OF POLITICAL PARTIES IN NEPAL’S PEACE BUILDING PROCESS - Cottle, Drew; Thapa, Sunil (PEOPLE: International Journal of Social Sciences, 2017)
After ten years of civil war in Nepal (1996 - 2006) the combatant forces brokered the Comprehensive Peace Accord (CPA). The war had ended but peace was never established and Nepal’s political economy remains weak and barely functioning. The CPA has been inoperative because of power struggles of the numerous parliamentary political parties in the post-insurgency Nepalese Governments. The political parties see no use for the CPA in these power struggles. Their sole and continuing objective is to secure political power. The causes of and the problems created by the civil war have been ignored in the power struggles of the parliamentary parties. The peace process in Nepal is now paralysed. The political parties have ignored, avoided, isolated and derailed the peace building process in Nepal. Hence, this paper analyses the political reality and the paralysed peace process in Nepal. It also examines how the activities of political parties have deliberately failed to bring the process of peace building to Nepal. And finally, it proposes practical peace building measures by which peace building could occur in Nepal which would bypass the power struggles of the political parties in Nepal.